Some Sedimentary Environment Characteristics in the Mong Cai Coastal Area, Quang Ninh Province, Vietnam - Loan, Bui Thi Thanh; Huy Hoang, Nguyen; Mai Luu, Nguyen; Van Nam, Le; Tien Dung, Pham; Dac Ve, Nguyen; Nhu Sieu, Le; Hoai Nhon, Dang; Duc Thanh, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 1, 2022)
The sedimentary environment characteristics in Mong Cai coastal area were assessed through pH, Eh, grain sizes, 226 Ra, 210 Pb, S‰, DO parameters. Mong Cai coastal area is mostly influenced by Ka Long river system that makes changes in the salinity, pH of water, pH and Eh of sediment, grain sizes, and sedimentation rates in the coastal area. There were six sediment types in the coastal area which were coarse sand, medium sand, fine sand, very fine sand, very coarse silt, and coarse silt. Fine sand was common in surface sediments; very fine sand was dominant in sediment core at Ka Long river mount; coarse silt and very coarse silt were common in sediment core at Mui Ngoc. The average sedimentation rate at the Ka Long river mouth (0.72 cm/year) was higher than that at the Mui Ngoc (0.27 cm/year). The sedimentary environment was divided into 3 groups, the first group was marine characteristics higher than the terrigenous characteristic, the second group was terrigenous characteristics higher than marine characteristics, and the third group was marine characteristics. In sediment cores showed 3 stages. In stage 1, distribution fine sand, very fine sand, and very coarse silt, from 52 to 80 cm at the Ka Long river mouth and from 40 to 52 cm at the Mui Ngoc. In stage 2, distribution of very coarse silt, coarse silt, from 38 to 52 cm (1947 - 1877) at Ka Long river mouth with sedimentation rate from 0.08 to 0.31 cm/year, at the Mui Ngoc from 12 to 40 cm (1944 (12 -14 cm)) with sedimentation rate of 0.09 cm/year. In stage 3, distribution very coarse silt, very fine sand, fine sand, from 0 to 38 cm (1919 - 1961) at the Ka Long river mouth with sedimentation rate of 0.34 - 1.62 cm/year, at the Mui Ngoc from 0 to 12 cm (2019 – 1966) with sedimentation rate of 0.07 - 0.51 cm/year.